The Effect of Circuit Exercise on Wall Climbing Speed on Speed Climbing Technique in Mapala Athlets University of PGRI Palembang - Saniatul Adewiyah; Bukman Lian; Tri Bayu Norito (JETISH: Journal of Education Technology Information Social Sciences and Health, 2002)
The problem of this research is that athletes do not have maximum speed in climbing speed climbing techniques. The purpose of the study was to determine the effect of circuit training on the speed of wall climbing in speed climbing techniques in mapala athletes at PGRI Palembang University. The research method is an experimental method of one group pretest-posttest design technique. The research population is 10 people and the sample is the total population. Data collection uses tests, with speed climbing technique speed test instruments. Data analysis used paired sample t test SPSS 16. The results of the study stated that there was an effect of circuit training on speed climbing wall speed climbing techniques in mapala athletes at PGRI Palembang University because Tcount T table (6.810 1.83).